1993
DOI: 10.1021/bi00065a025
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hydrogen bonding to lipid-lipid interactions in membranes and the role of lipid order: Effects of cholesterol, increased phospholipid unsaturation, and ethanol

Abstract: It is proposed that increased phospholipid unsaturation in membranes and perturbation by agents such as ethanol weaken interlipid hydrogen bonding involving water and that the process is independent of effects on lipid order. To investigate this, the rates of phospholipid desorption, as a measure of the strength of interlipid interactions, from "donor" lipid vesicles was determined. This was accomplished using (7-nitrobenzo-2-oxa-1,3-diazole-4-yl)aminohexanoate (C6-NBD) labeled phospholipids, the rate of desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
75
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 62 publications
19
75
0
1
Order By: Relevance
“…The precise orientation and location of the NBD group of this molecule in the membrane is known London, 1987, 1988;Mitra and Hammes, 1990;Wolf et al, 1992;Abrams and London, 1993). This group has been found to be localized at the membrane interface which has unique motional and dielectric characteristics distinct from both the bulk aqueous phase and the hydrocarbon-like interior of the membrane (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995) thus making it an ideal probe for monitoring red edge effects. Furthermore, previous electrophoretic measurements have shown that the NBD group in NBD-PE is uncharged at neutral pH in the membrane (Chattopadhyay and London, 1988).…”
Section: The Wavelength-selective Fluorescence Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise orientation and location of the NBD group of this molecule in the membrane is known London, 1987, 1988;Mitra and Hammes, 1990;Wolf et al, 1992;Abrams and London, 1993). This group has been found to be localized at the membrane interface which has unique motional and dielectric characteristics distinct from both the bulk aqueous phase and the hydrocarbon-like interior of the membrane (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995) thus making it an ideal probe for monitoring red edge effects. Furthermore, previous electrophoretic measurements have shown that the NBD group in NBD-PE is uncharged at neutral pH in the membrane (Chattopadhyay and London, 1988).…”
Section: The Wavelength-selective Fluorescence Approachmentioning
confidence: 99%
“…This not only results in the anisotropic behavior of the constituent lipid molecules, but more importantly, the environment of a probe molecule becomes very much dependent on its precise localization in the membrane. While the center of the bilayer is nearly isotropic, the upper portion, only a few angstroms away toward the membrane surface, is highly ordered (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995). As a result, properties such as polarity, fluidity, segmental motion, ability to form hydrogen bonds and extent of solvent (water) penetration would vary in a depth-dependent manner in the membrane (Fig.…”
Section: Wavelength-selective Fluorescence As a Membrane Dipstickmentioning
confidence: 99%
“…In addition, the physical properties of the surrounding phospholipid bilayer are known to modulate membrane function. Ethanol-induced changes in phospholipid hydrogen bonding have been observed to change acyl chain packing in pure lipid bilayers (5)(6)(7). Thus, the function of integral membrane receptors could be especially susceptible to the disruption of hydrogen-bonded water by ethanol.…”
mentioning
confidence: 99%
“…Water plays an extremely important role in the organization of the membrane bilayer and ethanol acts as a depressor of water activity. Slater et al, have shown that ethanol disrupts the role of the intra-membrane water and its inclusion leads to a decrease in a bilayer transition temperature [55].…”
Section: Discussionmentioning
confidence: 99%